Entrepreneurial And Market Orientation As A Strategy To Build Competitive Advantage And Marketing Performance Of Smes In Indonesia - Kasmirudin, Kasmiruddin; Heriyanto, Meyzi; Othman, Lie; Ruzikna, Ruzikna; Suryalena, Suryalena (International Journal of Science, Technology & Management, 2025)
The aim of the research is to analyze whether entrepreneurial orientation and market orientation as strategies for building competitive advantage have a positive effect on the marketing performance of Bukit Batu-Bengkalis Small and Medium Enterprises (SMEs). The research method used is the explanatory type, intended to test the research hypothesis. All Bukit Batu Small and Medium Enterprise entrepreneurs were used as the research population, and 36 SMEs were selected as research samples using purposive sampling techniques. The data analysis technique uses Partial Least Squares (PLS). The results of the study indicate that entrepreneurial orientation does not have a direct effect on marketing performance. In contrast, market orientation has a direct positive effect on marketing performance. In addition, competitive advantage also has a direct positive effect on marketing performance. Furthermore, entrepreneurial orientation has a positive effect on marketing performance through the mediation role of competitive advantage, while market orientation also has a positive effect on marketing performance through competitive advantage. The research results prove that entrepreneurial orientation and market orientation as strategies for building competitive advantage have a positive effect on the marketing performance of Bukit Batu-Bengkalis SMEs. It is recommended for Small and Medium Enterprise entrepreneurs to implement entrepreneurial and market-oriented behavior as a company strategy to build competitive advantage, in order to improve the marketing performance of SMEs.